A Generalized Interpolation Material Point Method for Shallow Ice Shelves. 2: Anisotropic Nonlocal Damage Mechanics and Rift Propagation. (24th August 2021) - Huth, Alex; Duddu, Ravindra; Smith, Ben
Abstract: Ice shelf fracture is responsible for roughly half of Antarctic ice mass loss in the form of calving and can weaken buttressing of upstream ice flow. Large uncertainties associated with the ice sheet response to climate variations are due to a poor understanding of these fracture processes and how to model them. Here, we address these problems by implementing an anisotropic, nonlocal integral formulation of creep damage within a large‐scale shallow‐shelf ice flow model. This model can be used to study the full evolution of fracture from initiation of crevassing to rifting that eventually causes tabular calving. While previous ice shelf fracture models have largely relied on simple expressions to estimate crevasse depths, our model parameterizes fracture as a progressive damage evolution process in three‐dimensions (3‐D). We also implement an efficient numerical framework based on the material point method, which avoids advection errors. Using an idealized marine ice sheet, we test the creep damage model and a crevasse‐depth based damage model, including a modified version of the latter that accounts for damage evolution due to necking and mass balance. We demonstrate that the creep damage model is best suited for capturing weakening and rifting over shorter (monthly/yearly) timescales, and that anisotropic damage reproduces typically observed fracture patterns better than isotropic damage. Because necking and mass balance can significantly influence damage on longer (decadal) timescales, we discuss the potential for a combined approach between models to best represent mechanical weakening and tabular calving within long‐term simulations. Plain Language Summary: Floating ice shelves buttress the flow of grounded ice into the ocean. Ice shelf fracture decreases this buttressing and in the form of calving, accounts for approximately half of Antarctic ice mass loss. Here, we introduce a "creep damage" framework that parameterizes large‐scale ice shelf fracture evolution in three‐dimensions (3‐D) and captures the weakening effect of fracture on flow. This framework is based on a previous approach for modeling individual crevasses, where the damage parameters were calibrated to laboratory tests. We use the material point method to avoid diffusion errors while transporting the damage field and ensure computational efficiency. Using an idealized ice configuration, we demonstrate that our methods represent fracture evolution ranging from crevasse initiation to rifting. We find that our modeled rift patterns best match typically observed patterns when we account for fracture orientation, or damage anisotropy. Furthermore, we show how a previously proposed damage framework that parameterizes crevasse depths is ill‐suited for modeling rifting, although it's modified form accounts for the impact of ice accumulation/melt and necking on damage, which we find is significant on decadal timescales. We conclude by discussing potential approaches for implementing these additional processes into the creep damage model. Key Points: Our shallow‐shelf creep damage model can represent the full evolution of ice shelf fracture from crevasse initiation to tabular calving Strongly anisotropic creep damage produces sharp, arcuate rift patterns more consistent with observations than isotropic creep damage The zero‐stress damage model poorly captures rifting, but a modified form accounts for damage evolution due to mass balance and necking